Scaling coefficient for three-dimensional grain coalescence of ZnO on Si(111) - Ruth, Marcel; Meier, Cedrik (Physical Review B)

Enhanced photoluminescence of colloidal nanocrystals embedded in epitaxially grown semiconductor microstructures - Kampmeier, J.; Rashad, M.; Woggon, U.; Ruth, M.; Meier, Cedrik; Schikora, D.; Lischka, K.; Pawlis, A. (Physical Review B)

Optical properties of cubic GaN from 1 to 20 eV - Feneberg, Martin; Röppischer, Marcus; Cobet, Christoph; Esser, Norbert; Schörmann, Jörg; Schupp, Thorsten; As, Donat Josef; Hörich, Florian; Bläsing, Jürgen; Krost, Alois; Goldhahn, Rüdiger (Physical Review B)

Mapping the near-field dynamics in plasmon-induced transparency - Ye, Ziliang; Zhang, Shuang; Wang, Yuan; Park, Yong-Shik; Zentgraf, Thomas; Bartal, Guy; Yin, Xiaobo; Zhang, Xiang (Physical Review B)

Control of plasmon dynamics in coupled plasmonic hybrid mode microcavities - Lanzillotti-Kimura, N. D.; Zentgraf, Thomas; Zhang, X. (Physical Review B)

Slow-light dispersion by transparent waveguide plasmon polaritons - Ishikawa, Atsushi; Oulton, Rupert F.; Zentgraf, Thomas; Zhang, Xiang (Physical Review B)

Polarization-dependent methanol adsorption on lithium niobate Z-cut surfaces - Riefer, A.; Sanna, S.; Schmidt, Wolf Gero (Physical Review B)

Atomic-resolution imaging of the polar (0001¯) surface of LiNbO3in aqueous solution by frequency modulation atomic force microscopy - Rode, S.; Hölscher, R.; Sanna, S.; Klassen, S.; Kobayashi, K.; Yamada, H.; Schmidt, Wolf Gero; Kühnle, A. (Physical Review B)

Fingerprints of order and disorder in the electronic and optical properties of crystalline and amorphous TiO2 - Landmann, M.; Köhler, T.; Köppen, S.; Rauls, E.; Frauenheim, T.; Schmidt, Wolf Gero (Physical Review B)

2-Aminopyrimidine-silver(I) based organic semiconductors: Electronic structure and optical response - Riefer, A.; Rauls, E.; Schmidt, Wolf Gero; Eberhard, J.; Stoll, I.; Mattay, J. (Physical Review B)

Many-body enhanced nonlinear conductance resonance in quantum channels - Han, Jong E.; Fischer, Saskia F.; Buchholz, Sven S.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D.; Bird, Jonathan P. (Physical Review B)

Generation and detection of mode-locked spin coherence in (In,Ga)As/GaAs quantum dots by laser pulses of long duration - Spatzek, S.; Varwig, S.; Glazov, M. M.; Yugova, I. A.; Schwan, A.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Edge-induced magnetoplasmon excitation in a two-dimensional electron gas under quantum Hall conditions - Notthoff, Christian; Reuter, Dirk; Wieck, Andreas D.; Lorke, Axel (Physical Review B)

Resonant nuclear spin pumping in (In,Ga)As quantum dots - Cherbunin, R. V.; Flisinski, K.; Gerlovin, I. Ya.; Ignatiev, I. V.; Kuznetsova, M. S.; Petrov, M. Yu.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Electrostatically trapping indirect excitons in coupled InxGa1−xAs quantum wells - Schinner, G. J.; Schubert, E.; Stallhofer, M. P.; Kotthaus, J. P.; Schuh, D.; Rai, A. K.; Reuter, Dirk; Wieck, A. D.; Govorov, A. O. (Physical Review B)

Combinedab initioand classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
Atomistic simulations on the silicon carbide precipitation in bulk silicon employing both, classical potential and first-principlesmethods are presented. The calculations aim at a comprehensive,microscopic understanding of the precipitation mechanism in the context of controversial discussions in the literature. For the quantum-mechanical treatment, basic processes assumed in the precipitation process are calculated in feasible systems of small size. The migration mechanism of a carbon 100 interstitial and silicon 11 0 self-interstitial in otherwise defect-free silicon are investigated using density functional theory calculations. The influence of a nearby vacancy, another carbon interstitial and a substitutional defect as well as a silicon self-interstitial has been investigated systematically. Interactions of various combinations of defects have been characterized including a couple of selected migration pathways within these configurations. Most of the investigated pairs of defects tend to agglomerate allowing for a reduction in strain. The formation of structures involving strong carbon–carbon bonds turns out to be very unlikely. In contrast, substitutional carbon occurs in all probability. A long range capture radius has been observed for pairs of interstitial carbon as well as interstitial carbon and vacancies. A rather small capture radius is predicted for substitutional carbon and silicon self-interstitials. Initial assumptions regarding the precipitation mechanism of silicon carbide in bulk silicon are established and conformability to experimental findings is discussed. Furthermore, results of the accurate first-principles calculations on defects and carbon diffusion in silicon are compared to results of classical potential simulations revealing significant limitations of the latter method. An approach to work around this problem is proposed. Finally, results of the classical potential molecular dynamics simulations of large systems are examined, which reinforce previous assumptions and give further insight into basic processes involved in the silicon carbide transition.

Tailoring the photonic band splitting in metallodielectric photonic crystal superlattices - Utikal, Tobias; Zentgraf, Thomas; Tikhodeev, Sergei G.; Lippitz, Markus; Giessen, Harald (Physical Review B)

Influence of Na adsorption on the quantum conductance and metal-insulator transition of the In-Si(111)(4×1)–(8×2) nanowire array - Schmidt, Wolf Gero; Babilon, M.; Thierfelder, C.; Sanna, S.; Wippermann, S. (Physical Review B)

Group-VII point defects in ZnSe - dos Santos, L. S.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Band offsets in cubic GaN/AlN superlattices - Mietze, C.; Landmann, M.; Rauls, E.; Machhadani, H.; Sakr, S.; Tchernycheva, M.; Julien, F. H.; Schmidt, Wolf Gero; Lischka, K.; As, Donat Josef (Physical Review B)

Asymmetric saddling of single porphyrin molecules on Au(111) - Müllegger, S.; Rashidi, M.; Lengauer, T.; Rauls, E.; Schmidt, Wolf Gero; Knör, G.; Schöfberger, W.; Koch, R. (Physical Review B)

Combined ab initio and classical potential simulation study on silicon carbide precipitation in silicon - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

Barium titanate ground- and excited-state properties from first-principles calculations - Sanna, S.; Thierfelder, C.; Wippermann, S.; Sinha, T. P.; Schmidt, Wolf Gero (Physical Review B)

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Electron g-factor anisotropy in symmetric (110)-oriented GaAs quantum wells - Hübner, J.; Kunz, S.; Oertel, S.; Schuh, D.; Pochwała, M.; Duc, H. T.; Förstner, Jens; Meier, Torsten; Oestreich, M. (Physical Review B)
We demonstrate by spin quantum beat spectroscopy that in undoped symmetric (110)-oriented GaAs/AlGaAs single quantum wells, even a symmetric spatial envelope wave function gives rise to an asymmetric in-plane electron Land´e g-factor. The anisotropy is neither a direct consequence of the asymmetric in-plane Dresselhaus splitting nor a direct consequence of the asymmetric Zeeman splitting of the hole bands, but rather it is a pure higher-order effect that exists as well for diamond-type lattices. The measurements for various well widths are very well described within 14 × 14 band k·p theory and illustrate that the electron spin is an excellent meter variable for mapping out the internal—otherwise hidden—symmetries in two-dimensional systems. Fourth-order perturbation theory yields an analytical expression for the strength of the g-factor anisotropy, providing a qualitative understanding of the observed effects.
Keywords: tet_topic_qw

Dirac point and edge states in a microwave realization of tight-binding graphene-like structures - Kuhl, U.; Barkhofen, Sonja; Tudorovskiy, T.; Stöckmann, H.-J.; Hossain, T.; de Forges de Parny, L.; Mortessagne, F. (Physical Review B)

Spin dynamics of electrons and holes inInGaAs/GaAsquantum wells at millikelvin temperatures - Fokina, L. V.; Yugova, I. A.; Yakovlev, D. R.; Glazov, M. M.; Akimov, I. A.; Greilich, A.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Control of the transmission phase in an asymmetric four-terminal Aharonov-Bohm interferometer - Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Bell, Matthew; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Phase shifts and phaseπjumps in four-terminal waveguide Aharonov-Bohm interferometers - Kreisbeck, Christoph; Kramer, Tobias; Buchholz, Sven S.; Fischer, Saskia F.; Kunze, Ulrich; Reuter, Dirk; Wieck, Andreas D. (Physical Review B)

Theory of phonon-mediated relaxation in doped quantum dot molecules - Grodecka-Grad, A.; Förstner, Jens (Physical Review B)
A quantum dot molecule doped with a single electron in the presence of diagonal and off-diagonal carrierphonon couplings is studied by means of a nonperturbative quantum kinetic theory. The interaction with acoustic phonons by deformation potential and piezoelectric coupling is taken into account. We show that the phonon-mediated relaxation is fast on a picosecond time scale and is dominated by the usually neglected off-diagonal coupling to the lattice degrees of freedom leading to phonon-assisted electron tunneling. We show that in the parameter regime of current electrical and optical experiments, the microscopic non-Markovian theory has to be employed.
Keywords: tet_topic_qd

Reentrant superconductivity in superconductor/ferromagnetic-alloy bilayers - Zdravkov, V. I.; Kehrle, J.; Obermeier, G.; Gsell, S.; Schreck, M.; Müller, C.; Krug von Nidda, H.-A.; Lindner, Jörg; Moosburger-Will, J.; Nold, E.; Morari, R.; Ryazanov, V. V.; et al. (Physical Review B)
We studied the Fulde-Ferrell-Larkin-Ovchinnikov-type state established due to the proximity effect in superconducting Nb/Cu_41Ni_59 bilayers. Using a special wedge-type deposition technique, series of 20–35 samples could be fabricated by magnetron sputtering during one run. The layer thickness of only a few nanometers, the composition of the alloy, and the quality of interfaces were controlled by Rutherford backscattering spectrometry, high-resolution transmission electron microscopy, and Auger spectroscopy. The magnetic properties of the ferromagnetic alloy layer were characterized with superconducting quantum interference device magnetometry. These studies yield precise information about the thickness and demonstrate the homogeneity of the alloy composition and magnetic properties along the sample series. The dependencies of the critical temperature on the Nb and Cu41Ni59 layer thickness, T_c(d_S) and T_c(d_F), were investigated for constant thickness d_F of the magnetic alloy layer and d_S of the superconducting layer, respectively. All types of nonmonotonic behaviors of T_c versus d_F predicted by the theory could be realized experimentally, from reentrant superconducting behavior with a broad extinction region to a slight suppression of superconductivity with a shallow minimum. Even a double extinction of superconductivity was observed, giving evidence for the multiple reentrant behavior predicted by theory. All critical temperature curves were fitted with suitable sets of parameters. Then, T_c(d_F) diagrams of a hypothetical ferromagnet/superconductor/ferromagnet spin-switch core structure were calculated using these parameters. Finally, superconducting spin-switch fabrication issues are discussed in detail in view of the achieved results.

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, Jörg; Schmidt, W. G.; Rauls, E. (Physical Review B)
A comparative theoretical investigation of carbon interstitials in silicon is presented. Calculations using classical potentials are compared to first-principles density-functional theory calculations of the geometries, formation, and activation energies of the carbon dumbbell interstitial, showing the importance of a quantummechanical description of this system. In contrast to previous studies, the present first-principles calculations of the interstitial carbon migration path yield an activation energy that excellently matches the experiment. The bond-centered interstitial configuration shows a net magnetization of two electrons, illustrating the need for spin-polarized calculations.

Dynamics of photoexcitation and stimulated optical emission in conjugated polymers: A multiscale quantum-chemistry and Maxwell-Bloch-equations approach - Schumacher, Stefan; Galbraith, Ian; Ruseckas, Arvydas; Turnbull, Graham A.; Samuel, Ifor D. W. (Physical Review B)

Manganese-hydrogen complexes inGa1−xMnxN - Bihler, C.; Gerstmann, Uwe; Hoeb, M.; Graf, T.; Gjukic, M.; Schmidt, Wolf Gero; Stutzmann, M.; Brandt, M. S. (Physical Review B)

Defects in carbon implanted silicon calculated by classical potentials and first-principles methods - Zirkelbach, F.; Stritzker, B.; Nordlund, K.; Lindner, J. K. N.; Schmidt, Wolf Gero; Rauls, E. (Physical Review B)

First-principles study of water adsorption and a high-density interfacial ice structure on(1×1)-O/Rh(111) - Thierfelder, C.; Schmidt, Wolf Gero (Physical Review B)

Lithium niobateX-cut,Y-cut, andZ-cut surfaces fromab initiotheory - Sanna, Simone; Schmidt, Wolf Gero (Physical Review B)

Chemical reactivity on surfaces: Modeling the imide synthesis from DATP and PTCDA on Au(111) - Rauls, E.; Blankenburg, S.; Schmidt, Wolf Gero (Physical Review B)

Wannier-function approach to spin excitations in solids - Şaşıoğlu, Ersoy; Schindlmayr, Arno; Friedrich, Christoph; Freimuth, Frank; Blügel, Stefan (Physical Review B)
We present a computational scheme to study spin excitations in magnetic materials from first principles. The central quantity is the transverse spin susceptibility, from which the complete excitation spectrum, including single-particle spin-flip Stoner excitations and collective spin-wave modes, can be obtained. The susceptibility is derived from many-body perturbation theory and includes dynamic correlation through a summation over ladder diagrams that describe the coupling of electrons and holes with opposite spins. In contrast to earlier studies, we do not use a model potential with adjustable parameters for the electron-hole interaction but employ the random-phase approximation. To reduce the numerical cost for the calculation of the four-point scattering matrix we perform a projection onto maximally localized Wannier functions, which allows us to truncate the matrix efficiently by exploiting the short spatial range of electronic correlation in the partially filled d or f orbitals. Our implementation is based on the full-potential linearized augmented-plane-wave method. Starting from a ground-state calculation within the local-spin-density approximation (LSDA), we first analyze the matrix elements of the screened Coulomb potential in the Wannier basis for the 3d transition-metal series. In particular, we discuss the differences between a constrained nonmagnetic and a proper spin-polarized treatment for the ferromagnets Fe, Co, and Ni. The spectrum of single-particle and collective spin excitations in fcc Ni is then studied in detail. The calculated spin-wave dispersion is in good overall agreement with experimental data and contains both an acoustic and an optical branch for intermediate wave vectors along the [100] direction. In addition, we find evidence for a similar double-peak structure in the spectral function along the [111] direction. To investigate the influence of static correlation we finally consider LSDA+U as an alternative starting point and show that, together with an improved description of the Fermi surface, it yields a more accurate quantitative value for the spin-wave stiffness constant, which is overestimated in the LSDA.

Modeling excitonic line shapes in weakly disordered semiconductor nanostructures - Kuznetsova, I.; Gőgh, N.; Förstner, Jens; Meier, Torsten; Cundiff, S. T.; Varga, I.; Thomas, P. (Physical Review B)
Excitonic spectra of weakly disordered semiconductor heterostructures are simulated on the basis of a one-dimensional tight-binding model. The influence of the length scale of weak disorder in quantum wells on the redshift of the excitonic peak and its linewidth is studied. By calculating two-dimensional Fouriertransform spectra we are able to determine the contribution of disorder to inhomogeneous and also to homogeneous broadenings separately. This disorder-induced dephasing is related to a Fano-type coupling and leads to contributions to the homogeneous linewidth that depends on energy within the inhomogeneously broadened line. The model includes heavy- and light-hole excitons and yields smaller inhomogeneous broadening for the light-hole exciton if compared to the heavy-hole exciton, which agrees qualitatively with the experiment.
Keywords: tet_topic_qw

Microscopic analysis of charge and spin photocurrents injected by circularly polarized one-color laser pulses in GaAs quantum wells - Duc, Huynh Thanh; Förstner, Jens; Meier, Torsten (Physical Review B)
The dynamics of charge and spin injection currents excited by circularly polarized, one-color laser beams in semiconductor quantum wells is analyzed. Our microscopic approach is based on a 14x14 k · p band-structure theory in combination with multisubband semiconductor Bloch equations which allows a detailed analysis of the photogenerated carrier distributions and coherences in k space. Charge and spin injection currents are numerically calculated for [110]- and [001]-grown GaAs quantum wells including dc population contributions and ac contributions that arise from intersubband coherences. The dependencies of the injection currents on the excitation conditions, in particular, the photon energy are computed and discussed.
Keywords: tet_topic_qw

Efficient implementation of the GW approximation within the all-electron FLAPW method - Friedrich, Christoph; Blügel, Stefan; Schindlmayr, Arno (Physical Review B)
We present an implementation of the GW approximation for the electronic self-energy within the full-potential linearized augmented-plane-wave (FLAPW) method. The algorithm uses an all-electron mixed product basis for the representation of response matrices and related quantities. This basis is derived from the FLAPW basis and is exact for wave-function products. The correlation part of the self-energy is calculated on the imaginary-frequency axis with a subsequent analytic continuation to the real axis. As an alternative we can perform the frequency convolution of the Green function G and the dynamically screened Coulomb interaction W explicitly by a contour integration. The singularity of the bare and screened interaction potentials gives rise to a numerically important self-energy contribution, which we treat analytically to achieve good convergence with respect to the k-point sampling. As numerical realizations of the GW approximation typically suffer from the high computational expense required for the evaluation of the nonlocal and frequency-dependent self-energy, we demonstrate how the algorithm can be made very efficient by exploiting spatial and time-reversal symmetry as well as by applying an optimization of the mixed product basis that retains only the numerically important contributions of the electron-electron interaction. This optimization step reduces the basis size without compromising the accuracy and accelerates the code considerably. Furthermore, we demonstrate that one can employ an extrapolar approximation for high-lying states to reduce the number of empty states that must be taken into account explicitly in the construction of the polarization function and the self-energy. We show convergence tests, CPU timings, and results for prototype semiconductors and insulators as well as ferromagnetic nickel.

Ultranarrow coupling-induced transparency bands in hybrid plasmonic systems - Zentgraf, Thomas; Zhang, Shuang; Oulton, Rupert F.; Zhang, Xiang (Physical Review B)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Collective single-mode precession of electron spins in an ensemble of singly charged (In,Ga)As/GaAs quantum dots - Greilich, A.; Spatzek, S.; Yugova, I. A.; Akimov, I. A.; Yakovlev, D. R.; Efros, Al. L.; Reuter, Dirk; Wieck, A. D.; Bayer, M. (Physical Review B)

Inversion-asymmetry-induced spin splitting observed in the quantum oscillatory magnetization of a two-dimensional electron system - Wilde, M. A.; Reuter, Dirk; Heyn, Ch.; Wieck, A. D.; Grundler, D. (Physical Review B)

Conversion of bound excitons to free excitons by surface acoustic waves - Völk, S.; Wixforth, A.; Reuter, Dirk; Wieck, A. D.; Ebbecke, J. (Physical Review B)

Measurement of the Knight field and local nuclear dipole-dipole field in an InGaAs/GaAs quantum dot ensemble - Auer, T.; Oulton, R.; Bauschulte, A.; Yakovlev, D. R.; Bayer, M.; Verbin, S. Yu.; Cherbunin, R. V.; Reuter, Dirk; Wieck, A. D. (Physical Review B)

Carrier relaxation dynamics in self-assembled semiconductor quantum dots - Kurtze, H.; Seebeck, J.; Gartner, P.; Yakovlev, D. R.; Reuter, Dirk; Wieck, A. D.; Bayer, M.; Jahnke, F. (Physical Review B)

Water adsorption on the α-Al2O3(0001) surface - Thissen, P.; Grundmeier, G.; Wippermann, S.; Schmidt, Wolf Gero (Physical Review B)